Androidal Fat Dominates in Predicting Cardiometabolic Risk in Postmenopausal Women. (30th November 2010) - Matvienko, O. A.; Alekel, D. L.; Bhupathiraju, S. N.; Hofmann, H.; Ritland, L. M.; Reddy, M. B.; Van Loan, M. D.; Perry, C. D.
Abstract : We hypothesized that soy isoflavones would attenuate the anticipated increase in androidal fat mass in postmenopausal women during the 36-month treatment, and thereby favorably modify the circulating cardiometabolic risk factors: triacylglycerol, LDL-C, HDL-C, glucose, insulin, uric acid, C-reactive protein, fibrinogen, and homocysteine. We collected data on 224 healthy postmenopausal women at risk for osteoporosis (45.8–65 y, median BMI 24.5) who consumed placebo or soy isoflavones (80 or 120 mg/d) for 36 months and used longitudinal analysis to examine the contribution of isoflavone treatment, androidal fat mass, other biologic factors, and dietary quality to cardiometabolic outcomes. Except for homocysteine, each cardiometabolic outcome model was significant (overallP -values from ≤.0001 to .0028). Androidal fat mass was typically the strongest covariate in each model. Isoflavone treatment did not influence any of the outcomes. Thus, androidal fat mass, but not isoflavonetreatment, is likely to alter the cardiometabolic profile in healthy postmenopausal women.